A New Zebrafish Model for Pseudoxanthoma Elasticum - Czimer, Dávid; Porok, Klaudia; Csete, Dániel; Gyüre, Zsolt; Lavró, Viktória; Fülöp, Krisztina; Chen, Zelin; Gyergyák, Hella; Tusnády, Gábor E.; Burgess, Shawn M.; Mócsai, Attila; Váradi, András; et al. (Frontiers in Cell and Developmental Biology, 2021)
Calcification of various tissues is a significant health issue associated with aging, cancer and autoimmune diseases. There are both environmental and genetic factors behind this phenomenon and understanding them is essential for the development of efficient therapeutic approaches. Pseudoxanthoma elasticum (PXE) is a rare genetic disease, a prototype for calcification disorders, resulting from the dysfunction of ABCC6, a transport protein found in the membranes of cells. It is identified by excess calcification in a variety of tissues (e.g. eyes, skin, arteries) and currently it has no cure, known treatments target the symptoms only. Preclinical studies of PXE have been successful in mice, proving the usefulness of animal models for the study of the disease. Here we present a new zebrafish (Danio rerio) model for PXE. By resolving some ambiguous assemblies in the zebrafish genome, we show that there are two functional and one non-functional paralogs for ABCC6 in zebrafish (abcc6a, abcc6b.1 and abcc6b.2, respectively). We created single and double mutants for the functional paralogs and characterized their calcification defects with a combination of techniques. Our results support a role for abcc6a in zebrafish calcification and suggest that the impairment of abcc6b.1 does not affect this biological process.